Lived Experiences of Physicians Working in Hospitals during the COVID-19 Crisis: A Qualitative Study - Ali Asghar Hayat; Ahmad Kalateh Sadati; Seyed Taghi Heydari; Ghobad Ramezani; Mohammad Hasan Keshavarzi (Kerman University of Medical Sciences, 2023)
Background: With the onset of the coronavirus pandemic in 2019, healthcare workers were at the forefront of dealing with the disease. Medical centers were faced with limited facilities and insufficient information. A number of medical staff became infected with the disease, and some lost their lives. This study was conducted to understand the perceived impact of the pandemic on physicians working in healthcare facilities of Shiraz and Yazd Universities of Medical Sciences during the COVID-19 pandemic.Methods: The present study was a qualitative one conducted in the teaching hospitals of Shiraz and Yazd in the southwest of Iran in 2020-2021. Purposive sampling was used to select the participants and the process continued until data saturation was reached. Data were collected through semi-structured interviews with 21 physicians working in hospital wards during the COVID-19 crisis. Data were analyzed using the seven-step analytical method proposed by Colaizzi.Results: Four themes and eleven subthemes emerged from data analysis. The main themes included managerial weakness, burnout, distorted doctor-patient relationship, and misinfodemic.Conclusion: The preparedness of the medical system and the infrastructure needed to deal with the coronavirus pandemic were not as expected. The COVID-19 crisis also highlighted the lack of information and support for physicians as a significant challenge.